Standard compliance and suitability of classroom capacity in secondary school buildings. Issue 3 (1st July 2019) - Norazman, Norsafiah; Che-Ani, Adi Irfan; Ja'afar, Nor Haslina; Khoiry, Muhamad Azry
Abstract : Purpose: Teaching and learning processes are conducted formally in a classroom as the main learning space for schooling system, where it should be implemented effectively to achieve a desired level of satisfaction and comfort for the students. To encourage and sustain students' motivation for continuous learning, specifically at secondary school level, classroom capacity is increasing significantly. The purpose of this paper is to analyse the guidelines and regulations of building design standard compliance, specifically for classrooms, and suggest the suitability of classroom capacity based on two main courses offered at the secondary school level. Design/methodology/approach: Two sets of perimeters were used in this study to gauge the intended results, namely, mixed method was used to carry out the study. The first indicator was a quantitative method whereby the current area of 20 selected classrooms (length × width) was physically measured and recorded. The second indicator used was a qualitative method, through a semi-structured interview. Findings: The findings showed that 55 per cent of classroom capacity in secondary school buildings complied with the existing guidelines, the stipulated design regulations and the classroom area requirement. The current area of classroom standing is at 2.25 m 2 per student with an observable increase in students' satisfaction during the teaching and learning processes. However, the findings from the semi-structured interview highlighted interesting points in relation to the suitability of classroom capacity. The teachers felt that classroom capacity affected performance of students based on two categories, namely, classroom-centred learning and classroom-less learning. The respondents agreed that the classroom-centred learning approach and classroom-less learning approach worked best with a maximum of 22 and 30 students per classroom, respectively. Originality/value: This paper provides the current information, knowledge and findings related with real classroom capacity at a secondary school building that may affect students' performance, while focus had always been on types of classroom, gadgets and qualified teaching staff. Hardly any valuable attention is given to the space these students spend almost a good part of their day for the rest of the week, over their formative learning period. Perhaps like the model of cars and sitting capacity, model classroom area and maximum capacity explored to ensure objectives irrespective of the driver, the teacher of the class. Therefore, these indicators may assist the school building management, building facilities and other professionals to identify and implement suitable of classroom capacity especially for all classroom-based learning in the schools generally.